A creche "IGNÁCIO DE LOYOLA TORRES" (1966-1997) e o berçário municipal "MÃE CRISTINA" (1997-2013) na história da educação infantil em Marilia/SP - Marquizeli, Josiane de Moura Dias (Editora Oficina Universitária, 2020)
Why learn about the history of early childhood education in the city of Marília/SP, in particular, the Creche "Ignácio de Loyola Torres" and the Municipal Nursery "Mãe Cristina"? These are questions that guided Josiane de Moura Dias Marquizeli's master's research, the results of which are published in this book. Taking the early childhood education institution where she worked as the object of study, the author developed rigorous documentary and bibliographical research, contributing to the understanding of aspects hitherto little or not explored in the history of early childhood education in Marília. Through knowledge of the past, the research made it possible to understand the present and the debates and actions that took place since at least the 1990s for the recognition of the right of young children to more than being cared for. There have been many advances, but there are still many needs and urgencies for this right to be fully implemented. Civil society plays an important role in this process. And the results of Josiane's research also contribute to this. This is, therefore, an indispensable book for teachers, caregivers, school and public education managers, researchers, undergraduate and graduate students, fathers and mothers. And it can also be considered as another instrument of struggle and an invitation to the necessary debate and urgent collective actions in defense of the education of our children for the construction of a fairer and more inclusive society.